”Se on aina elämys, kun pääsee kauppaan” – Kaupunkikeskusta ikääntyneiden fyysisenä ja sosiaalisena asiointiympäristönä - Koistinen Katri; Kohijoki Anna-Maija (Suomen maantieteellinen seura, 2025)
Urban population ageing has significant implications for city centres to cater to an increasing number of older citizens. This article focuses on the city centre from the older consumers’ (aged 60+) perspective, emphasising physical and social elements in the retail and service environment. The focus-group research method was used to identify what is an age-friendly city centre that supports older consumers in running their errands. The study proved the superiority of the city centre to the older consumers. It offers an opportunity to be outdoors, enjoy the visual elements and social interactions while running errands. A wide variety of age-friendly services and the possibility of combining different activities into one visit were found to attract older consumers. The study highlights that shopping is a vital activity that promotes active and healthy ageing. Thus, older people should be respected as consumers with heterogeneous needs and preferences when creating an age-friendly city centre.